Military Expenditure and Security Outcome Convergence in Africa: An Application of the Club Clustering Approach. Issue 3 (2nd July 2020) - Saba, Charles Shaaba
ABSTRACT: This study investigates the degree of convergence in military expenditure and security outcomes for a panel of 34 African countries spanning the period 1995 to 2015. We apply the Phillips and Sul methodology. Overall, the results reveal no evidence among African countries to suggest that military expenditure and security outcomes converge. The results of the analysis show that there exist: (i) three convergence clubs for military expenditure; (ii) one convergence club for security outcome. These findings imply that African countries are at different levels of military expenditure and the resultant security outcomes.